Working with children with migrant experience – a case study of the organization Stadtpiraten Freiburg e.V. in Freiburg im Breisgau, Germany - Edyta Januszewska; Urszula Markowska-Manista (Studia z Teorii Wychowania)
It is the objective of this article to present the case study of a non-governmental organisation conducting supportive activities for the benefit of children with the experience of immigration in Freiburg im Breisgau in Germany. In this article, the theoretical context depicting the policy of the intercultural opening of services and institutions to immigrants and refugees, and also the conception of ’interinclusion’ in the policy of intercultural opening, is presented. In the further part of this article, the analysis of the practical activities of the non-profit organisations as exemplified by Stadtpiraten Freiburg e.V. in the context of the presumptions behind the policy of the intercultural opening of services and institutions is presented in more of a detail.